Graft copolymerization of methyl methacrylate onto oil palm empty fruit bunch - Nur Syuhada, Ramli (2010)
Graft copolymerization of Methyl Methacrylate (MMA) onto Oil Palm Empty fruit Bunch (OPEFB) fiber has been successfully carried out using hydrogen peroxide (H2O) as an initiators and ferrous ammonium sulfate as catalyst in an aqueous medium. The effects of reaction temperature, reaction period and amount of initiators on the percentage of grafting were investigated. The results show that the percentage of grafting depends on reaction period and temperature as well as amount of initiator. The maximum percentage of grafting was obtained when the reaction was carried out using 5.00×102-3mol of H20.The optimum reaction period was 120 minutes and the reaction temperature was 65⁰C. The highest percentage of grafting and grafting efficiency was 30.51% and 85.30% respectively under optimum conditions. The presence of the functional group in the grafted polymers was characterized by FTIR spectroscopy and scanning electron microscope. The increasing in intensity at band 1730 cm 2-1 indicates that the MMA was grafted successfully on OPEFB.